A Vehicle of Punishment? Prison Diets in Belgium Circa 1900. (2nd January 2017) - Maes, Eric; Vanhouche, An-Sofie; Scholliers, Peter; Beyens, Kristel
Abstract: For decades institutional food has been studied to learn about wider developments in foodways in the past and present. Prison diets offer additional value to these studies in that prisoners' food has specific connotations (e.g., control or extra punishment) and that it should not exceed common diets outside the prison (the so-called less-eligibility principle). This interdisciplinary paper examines the Belgian prison system circa 1900, then one of the most advanced worldwide. It addresses two issues: how did prison diets relate to dietary trends outside, and how was food utilized inside of prisons in terms of functionality. The paper surveys prison diets in the second half of the nineteenth century, analyses and assesses the 1905 prison regime and compares it with contemporary norms. This paper contributes to the current debate concerning food and its relationship to detention.